Ionic Conductivity Test of Chitosan Solid Electrolyte Polymer Membrane with the Addition of Ionic Liquid - Multazam Multazam; Mohammad Ibnu Ridwan; Sun Theo C.L. Ndruru (Department of Chemistry - Universitas Bangka Belitung, 2024)
Lithium ion batteries are an alternative choice for fulfillment as an energy source. Beside that, lithium ion batteries are also use as energy storage. However, lithium ion batteries still use a liquid electrolyte which has the advantages of being toxic, explosive, and corrosive. So we need an alternative to replace liquid electrolyte, namely solid electrolyte membranes. The aim of this research is to determine the effect of adding ionic liquid [EMIm]Ac to chitosan polymer as a solid electrolyte polymer (SEP) membranes. Based on the resulta obtained, chitosan has been successfully isolated from chitin. Chitin isolated from shrimp shells. Based on the ionic conductivity value, the SEP membrane with the addition of 15% [EMIm]Ac ionic liquid has the highest ionic conductivity value, namely 5.02 x 10-5 S cm-1.